Evaluation outcomes of a long-running adult nutrition education programme - Pettigrew, Simone; Moore, S.; Pratt, Steve; Jongenelis, M. (Cambridge University Press, 2015)
Objective: For more than 20 years, the FOODcents adult nutrition education programme has been delivered to Western Australians. The aim of the programme is to provide disadvantaged individuals with the knowledge, skills and motivation to buy healthy foods on a limited budget. The present study evaluated whether the FOODcents curriculum and the way it is delivered are effective in improving participants’ nutrition-related knowledge and behaviours. Design: Evaluation data were collected via in-session pre–post questionnaires and a post-course online questionnaire. Setting: Western Australia. Subjects: Data were collected from participants attending just over one-half (54 %) of the FOODcents courses conducted over the two-year evaluation period. In total, 927 course participants provided usable data. Results: After exposure to the course, respondents demonstrated an improved ability to: (i) categorize foods according to the frequency with which they should be consumed and the proportion of the food budget that should be allocated to them; (ii) correctly interpret nutrition labels on food products; and (iii) appreciate the link between diet/obesity and a range of diseases. Improvements in the latter were especially pronounced among participants of low socio-economic status. In terms of behaviour change, significant improvements in fruit and vegetable consumption were reported, along with reductions in the consumption of fast food. Participants of low socio-economic status reported the greatest changes. Conclusions: The results indicate that the FOODcents nutrition education programme improves participants’ nutrition-related knowledge and behaviours.